2015
DOI: 10.1177/0363546515616802
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Injuries in Professional Hockey Players

Abstract: Most players are able to return to play in the NHL after an ACL injury. However, career length and performance may be significantly decreased compared with controls. This may represent a more severe initial injury, and more focused return-to-play pathways may identify barriers to return to play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 15 publications
5
49
0
1
Order By: Relevance
“…French alpine skiers who were younger at the time of injury were more likely to improve their performance after returning to sport 36. Playing position was not a significant determinant of returning to sport in American football,33 women’s basketball32 or women’s college soccer,39 but Sikka et al 37 found that NHL defenders were more likely to return to their previous level of performance than forwards and wings.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…French alpine skiers who were younger at the time of injury were more likely to improve their performance after returning to sport 36. Playing position was not a significant determinant of returning to sport in American football,33 women’s basketball32 or women’s college soccer,39 but Sikka et al 37 found that NHL defenders were more likely to return to their previous level of performance than forwards and wings.…”
Section: Resultsmentioning
confidence: 96%
“…However, college athletes injured during their fourth or fifth years at college were less likely to return to sport,21 39 and NHL players injured after turning 30 years of age were less likely to return to play at least one full season 37. French alpine skiers who were younger at the time of injury were more likely to improve their performance after returning to sport 36.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…19 National Basketball Association basketball players have shown to have a return to sport of 84.6% and a significant decrease in the number of games played in seasons 1 to 3 years after ACLR, although at 3 years they returned to their preinjury player efficiency rating. 20 The overall return to sport for National Collegiate Athletic Association Southeastern Conference women soccer players was 85%.…”
Section: Return-to-play Ratesmentioning
confidence: 99%